(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
Shell fishes constitute a vital source of food for humans due to its high nutritional values. Bacteriological and nutritional assessments of Galatea paradoxa treated with Citrus aurantifolia and NaCl were determined using bacteriological and analytical protocols. The results revealed a reduction from 4.845 to 2.301 Log CFU/g in Total Heterotrophic Bacterial Counts (THBC) in G. paradoxa treated with 10% NaCl for 5 mins. The G. paradoxa treated with 7.5 % NaCl for 5 min had a reduction in Total Coliform Counts (TCC) ranging from 3.903 to 2.398 Log CFU/g, while Total Faecal Coliform Counts (TFC) in G. paradoxa treated with 5 % and 10 % for 10 min reduced by 99.99 %. There was 53.46% THBC reduction in G. paradoxa treated with 10% C. aurantifolia for 5 min; THBC in G. paradoxa treated with 10% C. aurantifolia for 10 min reduced by 79.36 %; THBC in G. paradoxa treated with 10 % equal concentrations of NaCl and C. aurantifolia decreased by 99.99 % within 10 min, while TCC in G. paradoxa treated with 7.5 % equal concentrations of NaCl and C. aurantifolia within 10 min of exposure had 99.99 % decrease. The predominant survived bacterial genera in treated samples were Bacillus, Vibrio and Micrococcus. There was insignificant difference (p â‰¥ 0.05) between the nutritional compositions of treated and untreated samples. This study showed that G. paradoxa could be treated with C. aurantifolia and NaCl so as to avert possible foodborne diseases associated with consumption of this aquatic food.